Implantação em laboratório de cultivos de Moina micrura e Ceriodaphnia cornuta (Cladocera; Crustacea), espécies de cladóceras que ocorrem naturalmente em reservatórios do alto curso do rio Doce, nordeste brasileiro - Evangelista, Samuel de Araújo (2018)
To validate the use of organisms to be used in ecotoxicological tests, it is necessary to standardize the procedures of the cultures in the laboratory. Several of the standardized test organisms do not occur in Brazil and are not representative of the Brazilian ecosystem. The use of native species can increase the representativeness of the work developed with environmental samples. Cladocera are commonly used as test organisms in ecotoxicological trials, which is why it is necessary to know the ecology and systematics of these organisms. The objective of this work was to identify and implant the cultivation of the species Moina micrura and Ceriodaphnia cornuta, which occur naturally in reservoirs in the Brazilian northeast. After the identification of the organisms, tests were performed to verify the adaptability of Moina micrura to the laboratory conditions. At the same time, control charts were elaborated for M. micrura and C. cornuta, using NaCl as reference substance. In the laboratory conditions, it was verified that the water of the dam of the Agricultural School of Jundiaí presented better result for the cultivation. The NaCl sensitivity tests showed a 48h LC50 with values of 2.16g / L ± 0.44 for M. micrura and 1.89g / L ± 0.22 for C. cornuta.